Preservative Treatment of Keora (Sonneratia Apetala) Poles by Full Cell Method of Wood Preservation with CCA Preservative - Islam, MS; Ashaduzzaman, M; Islam, MH; Karim, MR; Hannah, MO (Bangladesh Journal of Scientific and Industrial Research, 2012)
Keora (Sonneratia apetala Buch. Ham.) poles which contain mostly sapwood (more that 61%) and are readily susceptible to wood destroying agents were used in the study. Keora poles were treated with 5.5% CCA-C type preservative by full cell method of wood preservation for the period of 2, 3, 4 and 5 hours with the treating pressure of 200 psi (1,379 kPa). The maximum penetration was 4.36 cm for 5 hours treating duration. Retention and penetration increased with the increase of treating duration. The total retentions of CCA preservative were 9.15 kg m-3 for 2 hours, 12.72 kg m-3 for 3 hours, 16.35 kg m-3 for 4 hours and 18.31 kg m-3 for 5 hours treating duration for sapwood dominated keora poles. Significant variation in penetration and retention was found in the statistical analysis for different treating durations. Key words: CCA-C preservative; Full-cell method; Penetration; Retention; Sonneratia apetala DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9585 BJSIR 2011; 46(4): 425-428